2007
DOI: 10.1055/s-2007-966896
|View full text |Cite
|
Sign up to set email alerts
|

A new stapler-based full-thickness transgastric access closure: results from an animal pilot trial

Abstract: Gastrotomy closure with a perorally delivered flexible stapling device created a leak-resistant transmural line of staples followed by full-thickness healing of the gastric wall incision. Increasing the length of the instrument and adding device articulation will further facilitate its use for NOTES procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 15 publications
(21 reference statements)
0
39
0
2
Order By: Relevance
“…In vivo survival studies proved the same success as a closing device [10,11,12]. This device was first presented in 2007 [13].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo survival studies proved the same success as a closing device [10,11,12]. This device was first presented in 2007 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of closure techniques using leak tests [12][13][14][15] currently represents the most objective and widely used method for determining the robustness of closure, and it is important that these studies be standardized and reproducible for multiple comparisons. A stapling device for closure of gastrotomy in NOTES has been reported previously [16,17], but to date, no published studies have evaluated closure of colotomy using a stapling device.…”
Section: Resultsmentioning
confidence: 99%
“…Marvin Ryou et al reported an ex vivo study that proved that double layer and purse-string suture are the strongest closures in a porcine model. Full thickness healing was observed after transgastric access closure with stapler-based device in experimental animals (three pigs) [41]. Leakage was not observed in this, however, limited study, which gives promise for development of secure closure technique and which is one of the main obstacles for NOTES.A working group created the theory that endoscopic suturing would be an essential skill for the therapist.…”
Section: Notes Updatementioning
confidence: 86%